Tracking Control for Hydrogen Fuel Cell Systems in Zero-Emission Ferry Ships - Mohammad Hassan Khooban; Navid Vafamand; Jalil Boudjadar (Complexity)
For more than a century, conventional marine vessels spatter the atmosphere with CO2 emissions and detrimental particles when operated by diesel motors/generators. Fuel cells have recently emerged as one of the most promising emission-free technologies for the electrification of ship propulsion systems. In fuel cell-based ship electrification, the entire marine power system is viewed as a direct current (DC) microgrid (MG) with constant power loads (CPLs). A challenge of such settings is how to stabilize the voltages and currents of the ship’s grid. In this paper, we propose a new modified backstepping controller to stabilize the MG voltage and currents. Finally, to study the performance and efficiency of our proposal, we run an experiment simulation using dSPACE real-time emulator.